KEPENTINGAN RUSIA BEKERJASAMA DENGAN INDONESIA DALAM BIDANG TEKNOLOGI ANTARIKSA - Rozi Maiza Putri; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study will explain about interest of Rusia agreed established outerspace cooperation with Indonesia and what are Rusia‟s goals from this cooperation. Rusia and Indonesia signed a cooperation agreement on Exploration and Utilization of Space for Peaceful Purposes on 1 December 2006. The areas of this cooperation include the field of launching space satellites, earth observation, satellite communications, satellite navigation, telemitri, tracking and control, rocket probe, facility space, material satellites, space science, training or education, and aeronautics technology.Researcher analyzed this case using qualitative methods to find data and facts through some literature. The literature collected from books, journals, mass media and websites. The theoretical framework applied in this research are realism perspective, national interests concept and also use international cooperation.This study shows the hidden interest is for the military purpose and actually to become the real objective of the development of space launch vehicle on the whole. This partnership is a step to improve the capacity of Rusia.Keywords: Rusia, Indonesia, National Interest, International Cooperation, Outer Space